2018
DOI: 10.1289/ehp2311
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated Ambient PM2.5-Induced Inflammation and Endothelial Dysfunction in a Murine Model of Neural IKK2 Deficiency

Abstract: Background:Exposure to ambient fine particulate matter (PM2.5) is associated with cardiovascular mortality, but underlying pathophysiologic mechanisms are not fully understood. Hypothalamic inflammation, characterized by the activation of Inhibitor kappaB kinase 2/Nuclear factor kappaB (IKK2/NF-κB) signaling pathway, may play an important role in the pathogenesis of cardiovascular diseases. We recently demonstrated that hypothalamic inflammation is increased in mice exposed to concentrated ambient PM2.5 (CAP).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 72 publications
7
21
0
Order By: Relevance
“…Our results are in accordance with previous studies that showed the pro-inflammatory effect of PM 2.5 in the hypothalamus 16,17,42 . Several elegant studies demonstrated that central IKKβ, which is part of the canonical TLR4 pathway, was likely involved in the inflammatory signals in the hypothalamus of mice exposed to PM 2.5 chronically.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results are in accordance with previous studies that showed the pro-inflammatory effect of PM 2.5 in the hypothalamus 16,17,42 . Several elegant studies demonstrated that central IKKβ, which is part of the canonical TLR4 pathway, was likely involved in the inflammatory signals in the hypothalamus of mice exposed to PM 2.5 chronically.…”
Section: Discussionsupporting
confidence: 94%
“…In another study, 16 weeks of PM 2.5 exposure increased pulmonary, systemic and adipose tissue inflammation as well as induced endothelial dysfunction. The deletion of IKKβ by using nestin cre and IKKβ flox flox mice decreased these inflammatory responses 16,17,42 . So far, these mentioned studies have focused on effects of chronic exposure to PM 2.5 on the peripheral disarrangements.…”
Section: Discussionmentioning
confidence: 99%
“…These clusterings strongly suggest that chronic CAP exposure markedly altered the circulating metabolome. They are consistent with numerous previous studies showing that chronic ambient PM 2.5 exposure correlates with various systemic and/or extra-pulmonary effects (Chen et al, 2017;Chen et al, 2018;Gorr et al, 2014;Hu et al, 2017;Sancini et al, 2014;Zhang et al, 2017). Notably, in spite of those numerous studies investigating the toxicity of chronic ambient PM 2.5 exposure, its biomarker(s) has not yet been established.…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, C57Bl/6J female mice (3-week-old, 11/group and 22 in total) were purchased from the Animal Center of Fudan University (Shanghai, China) and acclimated in the animal facility for 2 weeks before exposure to FA or CAP. The group size of 11 was determined through the power analysis using the previously published effect of CAP exposure on the circulating IL-6 (Chen et al, 2018). As per the calculation with an online calculator (www.stat.ubc.ca/~rollin/stats/ssize/ n2.html), the statistic power is 0.9.…”
Section: Concentrated Ambient Pm 25 (Cap) or Filtered Air (Fa) Exposurementioning
confidence: 99%
“…has been associated with an increased risk for atherosclerosis, hypertension, cardiovascular diseases, and diabetes [2][3][4].…”
mentioning
confidence: 99%